Analysis of Business Actors' Perceptions of Intellectual Property Legal Protection in Digital Business - Fawaid, Bahrul; Manan, Ahmad Fikal; Indriyanto, Indriyanto (LifeSciFi, 2024)
The increasing problem of copyright and patent infringement in digital business has become a serious concern in recent years. This research explores the perceptions of digital business actors in Indonesia regarding the legal protection of intellectual property, particularly through criminal law enforcement against copyright and patent violations. In rapidly developing digital businesses, intellectual property such as copyrights and patents have become crucial assets for companies to maintain their competitive advantage. However, copyright and patent infringement in digital business presents serious challenges, especially with increasing technological advances and internet penetration. This research uses qualitative methods that focus on an in-depth analysis of the perceptions of digital business actors in Indonesia regarding criminal law enforcement on copyright and patent violations. Data collection was carried out through interviews with digital business actors using a semi-structured interview guide. Data analysis was carried out using thematic analysis. The research results show that digital business actors have a high awareness of the importance of IPR protection, but they still face big challenges related to protection that is not yet effective and often does not provide an adequate deterrent effect against copyright and patent infringement.